Construction phase engineering geological study in Modi Khola Hydroelectric Project, Parbat district, western Nepal - Paudel, T. R.; Dangol, V.; Sharma, R. H. (Journal of Nepal Geological Society, 1998)
Detailed engineering geological study is one of the basic requirement for the underground excavation and other infrastructural development works in the geotectonically active part of the Himalaya. Geological investigation directly relates with the sub-surface condition of rock and soil and their engineering properties. Underground excavation and construction of hydropower tunnels, dams, roads, irrigation canal and all foundation works without proper understanding of engineering geological parameters will not meet the requirements to design any safe, efficient and cost-effective infrastructure on and under the earth. In the Modi Khola Hydroelectric Project, a sound approach on geological condition is considered during construction. This paper deals with the details of the construction phase engineering geological study. It also explains the various geotechnical and geological study done to decide the Tunnel alignments and foundation of various structures in the project. As a result of study, previously designed structures and location of the Surge Tank and Penstock fixed at loose terrace and conglomerate deposit were shifted on the bedrock by designing a 40 m high vertical shaft and about 445 m long pressure tunnel. Previously designed long and curved tunnel alignment from vertical shaft is changed by a straight and better alternative alignment to reduce the tunnel length by about 35m. Similarly, detail geotechnical study of rock in the tunnel have direct impact on support design. Using the maximum advantage of self-supporting capacity of rocks, a big amount of cost in tunnel is also reduced by designing the tunnel support system based on Q-value of rocks. All such changes have provided safety to the project and also made more cost-effective.